(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Floating drug delivery system (FDDS) is the gastro retentive system that can remain in the stomach for many hours and can significantly prolong the gastric residence time of drugs. The aim of this study was to obtain controlled release floating capsules of captopril, as one of the most ACE inhibitor used to manage hypertension and congestive heart failure. Therefore we investigated the effect of three excepients (HPMCK4M, HPMC K100M, ethyl cellulose) on the floating time and release rate of the drug. The drug: polymer ratio used was (1/6). The prepared capsules have shown good flowability for more than eight hours. It was observed that as the molecular weight of HPMC increased the floating time and dug release decreased. However, mixing of different grades of HPMC improved the floating time and sustained drug release in compare with high viscosity polymer alone. The results revealed that EC could improve the floating time as well as the drug release. According to the findings of this investigation, the superior dissolution profiles achieved by mixing the three used polymers and the prepared capsules could float and prolong the drug release for 10 hours.